THE USE OF INFORMATION-GAP ACTIVITIES IN ENHANCING STUDENTS’ SPEAKING SKILL - Nurhartanto, Adhi; Wengrum, Tyas Desita; Brajannoto, Destoprani (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
Language is crucially important in human life. To be part of a community, language is most likely the easiest medium for humans to communicate with one another quickly and functionally. English is the medium of choice for 60% of the world's literacy. It is not an exaggeration to say that once a person has mastered English, he will have access to the entire world. When teaching students to communicate, the teacher should be able to entice them to practice speaking spontaneously. To encourage students to express themselves spontaneously, this study used Information Gap functions. The objectives of this research are to determine and describe whether using Information Gap activities has a significant impact on the students' speaking ability in the first semester of tenth grade at SMA X Lampung in 2022/2023. In this research, the experimental approach has been used, with 2 classifications chosen at random. One class served as the control group, while the other served as the experiment group. T-test was used to compare both classes when analyzing the data. The results of this research indicate that students who were taught using Information Gaps activities performed better in speaking than those who were taught using traditional techniques. It also implies that participating in Information Gap practices has a major impact on students' speaking ability at SMA X Lampung in the first semester of the tenth class in 2022/2023.